2016
DOI: 10.1136/bcr-2016-216488
|View full text |Cite
|
Sign up to set email alerts
|

Combining an antiviral with rituximab in EBV-related haemophagocytic lymphohistiocytosis led to rapid viral clearance; and a comprehensive review

Abstract: Epstein-Barr virus (EBV)-related haemophagocytic lymphohistiocytosis (EBVr-HLH) has a better prognosis when the virus is rapidly cleared, but the best antiviral approach is controversial. We present a patient to whom the therapeutic standard rituximab was co-administered with valacyclovir and an HLH-specific treatment with favourable viral and clinical responses. We conducted an extensive literature review and contacted several world reference centres and experts to inquire about their approaches and experienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…Antivirals are insufficient for EBV clearance, and there is no established best antiviral method. 22,23 Previous studies have revealed that rituximab can successfully reduce viral load in EBV-infected B cell-related HLH in Western countries. 22,24 However, EBV infection was predominantly found in T cells and/or natural killer cells in patients with HLH from China mainland and other East Asia areas.…”
Section: Resultsmentioning
confidence: 99%
“…Antivirals are insufficient for EBV clearance, and there is no established best antiviral method. 22,23 Previous studies have revealed that rituximab can successfully reduce viral load in EBV-infected B cell-related HLH in Western countries. 22,24 However, EBV infection was predominantly found in T cells and/or natural killer cells in patients with HLH from China mainland and other East Asia areas.…”
Section: Resultsmentioning
confidence: 99%
“…In our patient who is medically stable, we have elected to pursue a dexamethasone induction course while monitoring response to therapy. Besides plasma exchange and intravenous immunoglobulin, emerging therapies that warrant further clinical investigation include anti-IL-1, anti-TNF-α, anti-IFN-γ treatments [32] as well as kinase inhibitors [32], rituximab [38] and anti-virals [39].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies on the effects of different antiviral drugs on EBV have been conducted. Therefore, the importance of finding an effective antiviral drug or vaccine becomes increasingly evident [40, 42].…”
Section: Discussionmentioning
confidence: 99%